The East Asian Paradox: An Updated Position Statement on the Challenges to the Current Antithrombotic Strategy in Patients with Cardiovascular Disease - Kim, Hyun Kuk; Tantry, Udaya S.; Smith, Sidney C.; Jeong, Myung Ho; Park, Seung-Jung; Kim, Moo Hyun; Lim, Do-Sun; Shin, Eun-Seok; Park, Duk-Woo; Huo, Yong; Chen, Shao-Liang; Bo, Zheng; et al. (Thrombosis and haemostasis, 2021)
Abstract East Asian patients have reduced anti-ischemic benefits and increased bleeding risk during antithrombotic therapies compared with Caucasian patients. As potent P2Y 12 receptor inhibitors (e.g., ticagrelor and prasugrel) and direct oral anticoagulants are commonly used in current daily practice, the unique risk–benefit trade-off in East Asians has been a topic of emerging interest. In this article, we propose updated evidence and future directions of antithrombotic treatment in East Asian patients.